THERMO-MECHANICALLY MODIFICATION OF AMORPHOUS POLYESTER FIBRES: ІІ. CALORIMETRIC INVESTIGATIONS: THERMO-MECHANICALLY MODIFICATION OF AMORPHOUS POLYESTER FIBRES: ІІ. CALORIMETRIC INVESTIGATIONS - Velev, Valentin; Popov, Anton; Kyurkchiev, Pencho; Veleva, Lyubomira; Mateva, Rusalia (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The present work is devoted to the investigation of the structure developments in as-spun amorphous poly (ethylene terephthalate) (PET) occurred as a result of heat mechanical treatments. The deformation behavior of as-spun amorphous poly (ethylene terephthalate) (PET) yarns subjected to simultaneous thermal and mechanical treatments has been studied. It was found that the applied tensile force simultaneously with the linear heating of the studied PET yarns strongly affects the samples deformation behaviour. Differential scanning calorimetry (DSC) has been used to study the structural rearrangements in the thermo-mechanically processed PET fibers occurred as a result of the treatment structural changes. Have been established dependencies between the parameters of the thermal deformation experiment and occurred in the samples structural changes.